1979
DOI: 10.1063/1.325767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrostatic pressure up to 25 kbars on zinc oxide varistors—Static loading

Abstract: To date, zinc oxide varistors have been subjected to uniaxial compression to 5 kbars and hydrostatic pressures to 10 kbars. These results show a behavior between current and pressure empirically described by IL∼P7. This paper presents results of experiments in which zinc oxide varistors were subjected to hydrostatic compression up to 25 kbars. Results show a significant departure from previously reported results. The leakage current remains constant at first until a pressure of 6–7 kbars is attained. It then r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Representative results corresponding to effects (i) and (ii) as well as a novel effect, observed for the first time in this study, are shown by means of two selected sets of piezotronically shifted I – V curves in Figure . The sample treated in Figure a shows an increase of the current below the breakdown voltage with increasing mechanical stress in configuration P. This effect corresponds to case (i), and has already been obtained by others in the course of compressive tests on bulk specimens . In configuration O, the same specimen shows an inversion of the previously observed effect.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Representative results corresponding to effects (i) and (ii) as well as a novel effect, observed for the first time in this study, are shown by means of two selected sets of piezotronically shifted I – V curves in Figure . The sample treated in Figure a shows an increase of the current below the breakdown voltage with increasing mechanical stress in configuration P. This effect corresponds to case (i), and has already been obtained by others in the course of compressive tests on bulk specimens . In configuration O, the same specimen shows an inversion of the previously observed effect.…”
supporting
confidence: 82%
“…Up till now, only bulk varistor samples (containing millions of grains) were investigated under compressive stresses. They were exposed to uniaxial or hydrostatic pressure up to 400 MPa . Theoretically speaking, as a consequence of compressive stresses, some of the potential barriers in varistor specimens with randomly oriented grains are lowered; others are raised and some remain unmodified.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Theoretical and experimental studies showed that the impact of the piezotronic effect in zinc oxide varistors strongly depends on the grain orientation, or in particular on the alignment of the polarization vector with respect to the GB. [8,[11][12][13][14][15] In varistor materials, the piezotronic effect occurs naturally due to the anisotropic thermal expansion coefficients in the aand c-direction of the wurtzite lattice and the resulting residual stresses during cooling down from sintering. Consequently, the electric resistance of GBs increases (i), decreases (ii), or becomes dependent on the direction of current flow across the barrier (iii).…”
mentioning
confidence: 99%
“…[10] However, on a macroscopic scale, e.g., in bulk varistors with at least several 10 000 grains, the mean materials behavior predominantly exhibits enhanced conductivity compared to the stress-free state. [8,[11][12][13][14][15] In varistor materials, the piezotronic effect occurs naturally due to the anisotropic thermal expansion coefficients in the aand c-direction of the wurtzite lattice and the resulting residual stresses during cooling down from sintering. [16] Therefore, polycrystalline varistor devices, with randomly oriented grains, are inevitably in a piezotronically "preconditioned" state.…”
mentioning
confidence: 99%